THE INHIBITION EFFECT OF MORINGA (Moringa oleifera L.) LEAVES AND RED GINGER RHIZOME (Zingiber officinale Rosc.) PT. "P" ETHANOL EXTRACT ON ENHANCEMENT SERUM CREATININE LEVELS OF MALE WISTAR RATS DYSLIPIDEMIA MODEL - Juliana Wijaya; Penny S Martioso; Sugiarto Puradisastra (Journal of Medicine and Health, 2023)
Elevation of serum creatinine levels is a biomarker of decreased kidney function. Dyslipidemia can decrease kidney function. Long-term consuming statins can increase creatinine levels. Moringa leaves (Moringa oleifera L.) and red ginger rhizomes (Zingiber officinale Rosc.) have antioxidant effects. Aim of study is to determine the inhibitory effect on increasing serum creatinine levels of concoction Moringa Leaves and Red Ginger Rhizome ethanol extract (CML-RGRE). True laboratory experimental study with completely randomized design was conducted on 30 male Wistar rat dyslipidemia models, induced by high-fat feeding (HFF)-Propylthiouracil (PTU) 0.01% for 21 days. Subjects were divided into six groups (n=5), Group I, II, III were treated CML-RGRE 135, 202.5, 270 mg/kg BW, IV dyslipidemia control, V Rosuvastatin 1.8 mg/kg BW, and VI fenofibrate 5.4 mg/kg BW, all still given HFF-PTU for 21 days. Serum creatinine levels (mg/dL) were measured 3 times, after acclimatization, created dyslipidemia models, and treatment using spectrophotometer, colorimetric kinetic methods. Data were analysed with paired t-test, ANOVA test, and Fischer's LSD, α = 0.05. All doses of CML-RGRE have effectively inhibited the increase serum creatinine levels (p < 0.01). Conclusion, Moringa Leaves and Red Ginger Rhizome ethanol extract effectively inhibited the increased serum creatinine levels of animal dyslipidemia models.